Preparation method of licorice flavone-loaded hydrogel and application thereof

CN122998045APending Publication Date: 2026-10-30ZHEJIANG CHINESE MEDICAL UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610924713.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-05-19
Filing Date
2026-06-25
Publication Date
2026-10-30

Smart Images

  • Figure CN122998045A_ABST
    Figure CN122998045A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of licorice flavone hydrogel preparation method and its application.The hydrogel is formed by the Schiff base reaction dynamic crosslinking of quaternary amine chitosan modified by gallic acid and oxidized dextran, and is loaded with licorice flavone.The hydrogel prepared in the present application has injectability, self-healing, tissue adhesion and good biocompatibility, can significantly prolong the residence time of licorice flavone in the stomach, realize slow, controllable sustained release, and improve its bioavailability.The hydrogel can effectively reduce the gastric mucosa damage of acute gastric ulcer rats induced by ethanol, reduce the ulcer area, reduce the level of inflammatory factors, and has no biological toxicity.The present application provides an efficient, safe natural drug delivery system for the treatment of acute gastric ulcer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, specifically to a multifunctional hydrogel loaded with glycyrrhizin flavonoids, its preparation method, and its application in the treatment of acute gastric ulcers. Background Technology

[0002] Acute gastric ulcer is a common digestive system disease, and its pathogenesis involves multiple pathological processes, including damage to the gastric mucosal barrier, oxidative stress, and inflammatory responses. Conventional clinical treatment mainly relies on chemical drugs such as proton pump inhibitors, which can temporarily relieve symptoms but have drawbacks such as strong drug dependence and significant side effects with long-term use. Studies show that traditional anti-ulcer drugs have limited effectiveness in repairing alcohol-induced gastric mucosal damage and cannot effectively address the problem of ulcer recurrence.

[0003] Glycyrrhiza flavonoids are an important class of active ingredients extracted and isolated from the traditional Chinese medicine licorice. They possess multiple pharmacological effects, including anti-inflammatory, antioxidant, and gastric mucosal protective properties. Their low toxicity and high safety profile significantly outperform chemical anti-ulcer drugs. Modern research indicates that glycyrrhiza flavonoids can effectively inhibit gastric acid secretion, enhance gastric mucosal barrier function, and reduce gastric mucosal damage by regulating inflammatory pathways, demonstrating unique advantages in the treatment of gastric ulcers. However, glycyrrhiza flavonoids suffer from poor water solubility and low bioavailability, severely limiting their clinical efficacy.

[0004] To address the technical bottleneck of poor water solubility, existing research often employs modified methods such as cyclodextrin inclusion and nanoemulsion. These methods either require the introduction of organic solvents, affecting biocompatibility, or are costly due to complex preparation processes, and generally suffer from low drug loading and poor stability. More critically, conventional delivery systems struggle to achieve targeted release and long-term retention of drugs at the ulcer site, failing to meet the specific requirements for controlled drug release in gastric ulcer treatment. Therefore, developing a novel delivery system that effectively improves the bioavailability of glycyrrhizin flavonoids while possessing good biocompatibility and intelligent release characteristics has become a pressing technical challenge in this field. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies, this invention provides a method for preparing glycyrrhizin-loaded hydrogels and their applications. In a first aspect, the present invention provides a method for preparing a hydrogel loaded with glycyrrhizin flavonoids, the method comprising the following steps: Step S1: Quaternized chitosan, gallic acid and crosslinking agent are reacted and freeze-dried to obtain gallic acid-modified quaternized chitosan; Step S2: Dextran reacts with an oxidizing agent and is freeze-dried to obtain oxidized dextran; Step S3: Dissolve the gallic acid-modified quaternized chitosan and the oxidized dextran in a buffer solution to obtain a gallic acid-modified quaternized chitosan solution and an oxidized dextran solution; dissolve glycyrrhizin in an organic solvent to obtain a glycyrrhizin solution. Step S4: Mix the gallic acid-modified quaternized chitosan solution, the oxidized dextran solution, and the glycyrrhizin solution together. After the reaction is complete, a hydrogel loaded with glycyrrhizin is obtained.

[0006] Further, the crosslinking agent in step S1 includes 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and / or N-hydroxysuccinimide.

[0007] Furthermore, the molar ratio of the quaternized chitosan, the gallic acid, the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and the N-hydroxysuccinimide is 1:1:1:1.

[0008] Further, the buffer solution in step S2 includes a phosphate buffer solution, and the organic solvent includes dimethyl sulfoxide.

[0009] Further, in step S3, the concentration of the gallic acid-modified quaternized chitosan solution is 10-30 mg / mL, the concentration of the oxidized dextran solution is 30-70 mg / mL, and the concentration of the glycyrrhizin flavonoid solution is 200-400 mg / mL.

[0010] Preferably, the concentration of the gallic acid-modified quaternized chitosan solution is 20 mg / mL, and the concentration of the oxidized dextran solution is 50 mg / mL.

[0011] Further, the gallic acid-modified quaternized chitosan solution and the oxidized dextran solution described in step S4 are mixed at a volume ratio of 1:1.

[0012] Secondly, the present invention provides a hydrogel loaded with glycyrrhizin obtained by the preparation method described above.

[0013] Thirdly, the present invention provides a pharmaceutical formulation comprising the aforementioned hydrogel loaded with glycyrrhizin and pharmaceutically acceptable excipients.

[0014] The beneficial effects of this invention are as follows: (1) This invention utilizes gallic acid to modify quaternized chitosan. Through the synergistic effect of the two components, a hydrogel with excellent self-healing properties and low swelling rate is successfully prepared. The self-healing ability of the hydrogel can ensure the structural stability of the hydrogel in the gastric environment, while the low swelling rate can prevent the drug from being released too quickly, providing a good carrier material for drugs with poor water solubility.

[0015] (2) The present invention constructs a hydrogel loaded with glycyrrhizin, which can significantly prolong the retention time of glycyrrhizin in the stomach and achieve slow and controllable continuous release, thereby effectively improving the bioavailability of glycyrrhizin.

[0016] (3) The hydrogel loaded with glycyrrhizin constructed in this invention improves the concentration of drugs in the stomach through a long-term local delivery mechanism, significantly reduces gastric mucosal damage and shrinks the ulcer area, and provides a new, efficient and safe natural drug delivery solution for the treatment of gastric ulcers. Attached Figure Description

[0017] Figure 1 The NMR spectra of gallic acid-modified quaternary ammonium chitosan (QCS-GA) and oxidized dextran (OD) in Example 1 of this invention are shown. Figure 2 The infrared spectra of dextran, oxidized dextran (OD), quaternized chitosan and gallic acid-modified quaternized chitosan (QCS-GA) in Example 1 of the present invention are shown. Figure 3 The UV scanning results are for gallic acid, quaternary aminated chitosan, and gallic acid-modified quaternary aminated chitosan (QCS-GA) in Example 1 of this invention. Figure 4 The appearance of the OD / QCS-GA (OCG) hydrogel and the glycyrrhizin-loaded hydrogel (LF-OCG) in Example 1 of this invention, as well as the hydrogels in Examples 2-3; Figure 5 These are comparative graphs showing the self-healing performance tests of Embodiment 1 and Comparative Examples 1-3 of the present invention. Figure 6 This is a comparison chart of the swelling rates of Example 1 and Comparative Examples 1-3 of the present invention; Figure 7 These are scanning electron microscope images of the OCG and LF-OCG hydrogels prepared in Example 1 of this invention; Figure 8 The rheological curves of OCG and LF-OCG hydrogels in Example 1 of this invention are shown. Figure 9 The swelling ratios of the OCG and LF-OCG hydrogels in Example 1 of this invention; Figure 10 The graph shows the test results of the self-healing properties of OCG and LF-OCG hydrogels in Example 1 of this invention. Figure 11 This is a graph showing the injectionability evaluation results of OCG and LF-OCG hydrogels in Example 1 of the present invention; Figure 12 This is a diagram showing the biodistribution and retention of LF and LF-OCG hydrogels in Example 1 of the present invention; Figure 13This is an in vitro drug release curve of LF and LF-OCG hydrogels in gastric juice in Example 1 of the present invention; Figure 14 This is a graph showing the biocompatibility test results of the LF-OCG hydrogel in Example 1 of the present invention; Figure 15 This is a diagram showing the results of the LF-OCG hydrogel test on ethanol-induced GES-1 cell viability in Example 1 of this invention. Figure 16 The figure shows the test results of the effect of LF-OCG hydrogel on ethanol-induced intracellular ROS levels in GES-1 cells in Example 1 of this invention; Figure 17 Flowchart for drug administration in mouse modeling; Figure 18 Photographs and comparisons of the lesion area of ​​stomach tissue from rats in different treatment groups; Figure 19 Comparison of H&E staining results of gastric tissues from rats in different treatment groups; Figure 20 A comparison of pH values ​​in the gastric tissues of rats from different treatment groups; Figure 21 H&E staining of organ indices and sections of rats in different treatment groups; Figure 22 Statistical graph showing the content of inflammatory factors (TNF-α, IL-1β and IL-6) and oxidative indicators (GSH, SOD and MDA) in the gastric tissue of rats in different treatment groups. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0019] The reagents required for this invention are conventional experimental reagents, purchased from commercially available channels; the experimental methods not mentioned are conventional experimental methods and will not be described in detail here.

[0020] Example 1

[0021] 1. Preparation of hydrogel precursor materials Quaternized chitosan (QCS) was dissolved in deionized water to prepare a 10-15 mg / mL solution. Gallic acid (GA), EDC (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide), and NHS (N-hydroxysuccinimide) crosslinking agent were added in an equimolar ratio to the quaternized chitosan (i.e., the molar ratio of quaternized chitosan to gallic acid, EDC, and NHS was 1:1:1:1). After reacting at room temperature for 24 h, the mixture was purified by dialyzing and lyophilized to obtain gallic acid-modified quaternized chitosan (QCS-GA). Simultaneously, dextran was prepared into a 10-15 mg / mL aqueous solution, and sodium periodate was added at a mass ratio of 1:1. The mixture was reacted in the dark for 12 h, dialyzed, and then lyophilized to obtain oxidized dextran (OD).

[0022] The structure of the obtained hydrogel precursor material was identified, including infrared characterization, ultraviolet characterization, and nuclear magnetic resonance characterization. The methods and results are as follows: 1.1 NMR characterization: The chemical structures of OD and QCS-GA were determined using a Bruker 600 MHz nuclear magnetic resonance spectrometer. The samples were dissolved in deuterated solvents, and their ¹H-NMR and ¹³C-NMR spectra were recorded.

[0023] The results showed that the ¹H-NMR of OD exhibited complex multiplets of -CH2- / -CH- after the sugar ring opening at δ 3.0–4.0 ppm, and a weak aldehyde proton signal appeared at δ 9.0–9.8 ppm; its ¹³C-NMR showed a new aldehyde carbon resonance at δ 90–92 ppm, confirming the selective oxidation of NaIO4 to -CHO ( Figure 1 A). Quaternary ammonium groups (–N) appear at δ 3.0–3.2 ppm in the ¹H-NMR spectrum of QCS-GA. + The strong singlet of the (CH3)3) methyl hydrogen indicates that the structure remains stable during modification. A new signal belonging to the gallic acid benzene ring hydrogen appears at δ 6.8–7.2 ppm after modification. The characteristic peak of the quaternary ammonium methyl carbon is still present at δ 53–55 ppm in the ¹³C-NMR spectrum, while new signals of the gallic acid benzene ring carbon and ester bond carbon appear in the δ 130–150 and 165–170 ppm ranges, respectively. Figure 1 B). The above results indicate that gallic acid has been successfully grafted onto the quaternized chitosan molecule.

[0024] 1.2 Infrared characterization: The infrared spectral wavenumber range is 400-4000 cm⁻¹ -1 The spectrometer has a resolution of 4 cm⁻¹. -1 The signal-to-noise ratio is 50000:1, and the scan is performed 32 times.

[0025] Infrared characterization results showed that dextran only exhibited polysaccharide backbone fingerprint peaks (1200–950 cm⁻¹). -1 ); after oxidation treatment, oxidized dextran (Ox-Dextran) was obtained, and at 1643.6 cm⁻¹ -1 The characteristic absorption peak of carbonyl appears ( Figure 2 A) indicates that the oxidation reaction proceeded successfully. Quaternized chitosan was observed at 1471.6 cm⁻¹. -1 The characteristic absorption of the quaternary ammonium C–N bond is visible; after modification with gallic acid, its spectrum reaches 1555 cm⁻¹. -1 An aromatic ring C=C vibration peak appears at 1370.3 cm⁻¹. -1 An absorption band associated with the phenolic hydroxyl / ester C–O vibration appears at the amide region, accompanied by enhancement in the amide region. Figure 2 B), indicating that GA grafting was successful.

[0026] 1.3 Ultraviolet Characterization: Quaternary ammonium chitosan (QCS), gallic acid (GA), and the modified quaternary ammonium chitosan-gallic acid copolymer (QCS-GA) were dissolved in deionized water, and the whole wavelength was scanned in the range of 200–800 nm using a UV spectrophotometer.

[0027] The results showed that both GA and QCS-GA exhibited characteristic absorption peaks at approximately 260 nm, while QCS showed no significant absorption in this wavelength range, indicating that gallic acid had been successfully grafted onto the quaternized chitosan molecule via a reaction between the carboxyl and amino groups. (See results below.) Figure 3 As shown.

[0028] 2. Hydrogel Preparation A 20 mg / mL solution of gallic acid-modified quaternary ammonium chitosan (QCS-GA) (pH 6.8-7.4) was prepared using PBS, and a 50 mg / mL solution of oxidized dextran (OD) (pH 7.4) was prepared using PBS. Glycyrrhizin flavonoids (LF) were dissolved in DMSO to prepare a stock solution of 200-400 mg / mL. The QCS-GA and OD solutions were mixed at a 1:1 volume ratio, followed by the addition or omission of glycyrrhizin flavonoids solution to achieve a final concentration below 50 mg / mL, followed by vortexing. Within 5-8 minutes, the mixture underwent a Schiff base reaction to form injectable and self-healing QCS-GA-OD (OCG) blank hydrogels and glycyrrhizin-loaded hydrogels (LF-OCG).

[0029] Example 2

[0030] 1. Preparation of hydrogel precursor materials Quaternized chitosan (QCS) was dissolved in deionized water to prepare a 10-15 mg / mL solution. Gallic acid (GA), EDC (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide), and NHS (N-hydroxysuccinimide) crosslinking agent were added in an equimolar ratio to the quaternized chitosan (i.e., the molar ratio of quaternized chitosan to gallic acid, EDC, and NHS was 1:1:1:1). After reacting at room temperature for 24 h, the mixture was purified by dialyzing and lyophilized to obtain gallic acid-modified quaternized chitosan (QCS-GA). Simultaneously, dextran was prepared into a 10-15 mg / mL aqueous solution, and sodium periodate was added at a mass ratio of 1:1. The mixture was reacted in the dark for 12 h, dialyzed, and then lyophilized to obtain oxidized dextran (OD).

[0031] 2. Hydrogel Preparation A 10 mg / mL solution of gallic acid-modified quaternary ammonium chitosan (QCS-GA) (pH 6.8-7.4) was prepared using PBS, and a 30 mg / mL solution of oxidized dextran (OD) (pH 7.4) was prepared using PBS. Licorice flavonoids (LF) were dissolved in DMSO to prepare a stock solution of 200-400 mg / mL. The QCS-GA and OD solutions were mixed at a 1:1 volume ratio, followed by the addition of the licorice flavonoid solution to a final concentration below 50 mg / mL, and vortexed to mix. Within 5-8 minutes, the mixture formed an injectable and self-healing QCS-GA-OD (OCG) blank hydrogel via a Schiff base reaction.

[0032] Example 3

[0033] 1. Preparation of hydrogel precursor materials Quaternized chitosan (QCS) was dissolved in deionized water to prepare a 10-15 mg / mL solution. Gallic acid (GA), EDC (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide), and NHS (N-hydroxysuccinimide) crosslinking agent were added in an equimolar ratio to the quaternized chitosan (i.e., the molar ratio of quaternized chitosan to gallic acid, EDC, and NHS was 1:1:1:1). After reacting at room temperature for 24 h, the mixture was purified by dialyzing and lyophilized to obtain gallic acid-modified quaternized chitosan (QCS-GA). Simultaneously, dextran was prepared into a 10-15 mg / mL aqueous solution, and sodium periodate was added at a mass ratio of 1:1. The mixture was reacted in the dark for 12 h, dialyzed, and then lyophilized to obtain oxidized dextran (OD).

[0034] 2. Hydrogel Preparation A 10 mg / mL solution of gallic acid-modified quaternary ammonium chitosan (QCS-GA) (pH 6.8-7.4) was prepared using PBS, and a 30 mg / mL solution of oxidized dextran (OD) (pH 7.4) was prepared using PBS. Licorice flavonoids (LF) were dissolved in DMSO to prepare a stock solution of 200-400 mg / mL. The QCS-GA and OD solutions were mixed at a 1:1 volume ratio, followed by the addition of the licorice flavonoid solution to a final concentration below 50 mg / mL, and vortexed to mix. Within 5-8 minutes, the mixture formed an injectable and self-healing QCS-GA-OD (OCG) blank hydrogel via a Schiff base reaction. Figure 4 The macroscopic morphology of the hydrogels in Examples 1-3 is shown.

[0035] Comparative Example 1: Hydrogel made from gallic acid-modified carboxymethyl chitosan and oxidized dextran 1. Preparation of hydrogel precursor materials Carboxymethyl chitosan (CCS) was dissolved in deionized water to prepare a 10-15 mg / mL CCS solution. Gallic acid (GA), EDC, and NHS crosslinking agent were added in an equimolar ratio to CCS (i.e., the molar ratio of CCS to gallic acid, EDC, and NHS was 1:1:1:1). After reacting at room temperature for 24 h, the mixture was purified by dialyzing and lyophilized to obtain gallic acid-modified CCS-GA. Simultaneously, dextran was prepared into a 10-15 mg / mL aqueous solution, and sodium periodate was added at a mass ratio of 1:1. The mixture was reacted in the dark for 12 h, dialyzed, and then lyophilized to obtain oxidized dextran (OD).

[0036] Gallic acid grafting was successfully achieved through infrared and ultraviolet spectroscopy characterization.

[0037] 2. Preparation of hydrogels made from gallic acid-modified carboxymethyl chitosan and oxidized dextran Gallic acid-modified carboxymethyl chitosan (CCS-GA) was prepared into a 20 mg / mL solution (pH 6.8-7.4) using PBS, and oxidized dextran (OD) was prepared into a 50 mg / mL solution (pH 7.4) using PBS. The CCS-GA solution and the OD solution were mixed at a volume ratio of 1:1. The mixture formed a hydrogel of gallic acid-modified carboxymethyl chitosan and oxidized dextran, CCS-GA-OD, within 5-8 minutes through a Schiff base reaction.

[0038] The difference between the hydrogel obtained in Comparative Example 1 and the blank hydrogel obtained in Example 1 lies in the different chitosan modification groups.

[0039] Comparative Example 2: Hydrogels made from gallic acid-free quaternized chitosan and oxidized dextran 1. Preparation of hydrogel precursor materials Quaternized chitosan (QCS) was dissolved in deionized water to prepare a 10-15 mg / mL solution. EDC and NHS crosslinking agents were added in an equimolar ratio to the quaternized chitosan (i.e., the molar ratio of quaternized chitosan to EDC and NHS was 1:1:1). After reacting at room temperature for 24 h, the mixture was purified by dialyzing and lyophilized to obtain gallic acid-free quaternized chitosan (QCS). At the same time, dextran was prepared into a 10-15 mg / mL aqueous solution, and sodium periodate was added at a mass ratio of 1:1. The mixture was reacted in the dark for 12 h, dialyzed, and then lyophilized to obtain oxidized dextran (OD).

[0040] 2. Preparation of hydrogels made from gallic acid-modified carboxymethyl chitosan and oxidized dextran The gallic acid-free quaternized chitosan (QCS) was prepared into a 20 mg / mL solution (pH 6.8-7.4) using PBS, and the oxidized dextran (OD) was prepared into a 50 mg / mL solution (pH 7.4) using PBS. The QCS and OD solutions were mixed at a volume ratio of 1:1, and the mixture formed a hydrogel of gallic acid-free quaternized chitosan and oxidized dextran, QCS-OD, within 5-8 minutes via a Schiff base reaction.

[0041] The difference between the hydrogel obtained in Comparative Example 2 and the blank hydrogel obtained in Example 1 lies in whether or not it is modified with gallic acid.

[0042] Comparative Example 3: Hydrogels made from gallic acid-free carboxymethyl chitosan and oxidized dextran 1. Preparation of hydrogel precursor materials Carboxymethyl chitosan (CCS) was dissolved in deionized water to prepare a 10-15 mg / mL solution. EDC and NHS crosslinking agents were added in an equimolar ratio with quaternized chitosan (i.e., the molar ratio of CCS to EDC and NHS was 1:1:1). After reacting at room temperature for 24 h, the mixture was purified by dialyzing and lyophilized to obtain gallic acid-free CCS. Simultaneously, dextran was prepared into a 10-15 mg / mL aqueous solution, and sodium periodate was added at a mass ratio of 1:1. The mixture was reacted in the dark for 12 h, dialyzed, and then lyophilized to obtain oxidized dextran (OD).

[0043] 2. Preparation of hydrogels made from gallic acid-modified carboxymethyl chitosan and oxidized dextran The gallic acid-free carboxymethyl chitosan (CCS) was prepared into a 20 mg / mL solution (pH 6.8-7.4) using PBS, and the oxidized dextran (OD) was prepared into a 50 mg / mL solution (pH 7.4) using PBS. The CCS and OD solutions were mixed at a volume ratio of 1:1, and the mixture formed a hydrogel of gallic acid-free carboxymethyl chitosan and oxidized dextran, CCS-OD, within 5-8 minutes via a Schiff base reaction.

[0044] The difference between the hydrogel obtained in Comparative Example 3 and the blank hydrogel obtained in Example 1 lies in the different chitosan modification groups and the presence or absence of gallic acid modification.

[0045] The self-healing properties and swelling rates of the hydrogels QCS-GA-OD obtained in Example 1, CCS-GA-OD obtained in Comparative Example 1, QCS-OD obtained in Comparative Example 2, and CCS-OD obtained in Comparative Example 3 were tested. The experimental results are as follows: Self-healing properties: The hydrogels QCS-GA-OD obtained in Example 1, CCS-GA-OD obtained in Comparative Example 1, QCS-OD obtained in Comparative Example 2, and CCS-OD obtained in Comparative Example 3 were placed in culture dishes. The hydrogels were completely cut in half with a scalpel, and then the cut surfaces were put together. The hydrogels were left to stand at room temperature for a period of time to observe the changes in their appearance.

[0046] The results are as follows Figure 5 As shown, the QCS-GA-OD hydrogel obtained in Example 1 exhibits excellent self-healing properties, and the interface can restore structural integrity in a short time after cutting; while the CCG-GA-OD hydrogel obtained in Comparative Example 1 has limited repair ability under the same conditions, and there are obvious traces on the interface after repair, indicating that its network reconstruction ability is weak.

[0047] Meanwhile, the QCS-OD hydrogel obtained in Comparative Example 2 without gallic acid (GA) modification and the CCG-OD hydrogel obtained in Comparative Example 3 still showed significant differences in self-healing ability: the QCS-OD hydrogel obtained in Comparative Example 2 without gallic acid modification could still achieve self-repair; while the CCG-OD hydrogel obtained in Comparative Example 3 without gallic acid modification had obvious traces on the interface after repair and poor shape retention, and collapsed, deformed or over-spread under its own weight or small external force.

[0048] Based on the self-healing experiment results, the following conclusions can be drawn by comparing the healing abilities of different hydrogels: First, under the same modification conditions (i.e., whether or not gallic acid was used for modification), the self-healing properties of quaternized chitosan (QCS)-based hydrogels were superior to those of carboxymethyl chitosan (CCS)-based hydrogels. Specifically, the QCS-GA-OD hydrogel obtained in Example 1 exhibited stronger healing ability than the CCS-GA-OD hydrogel obtained in Comparative Example 1, and the QCS-OD hydrogel obtained in Comparative Example 2 exhibited stronger healing ability than the CCS-OD hydrogel obtained in Comparative Example 3. This indicates that the hydrogels formed by chitosan modified with quaternary ammonium groups have superior dynamic network reconstruction capabilities and structural stability.

[0049] Secondly, the self-healing ability of the hydrogels was further enhanced after introducing gallic acid (GA) modification onto the same chitosan backbone: the QCS-GA-OD hydrogel obtained in Example 1 was superior to the QCS-OD hydrogel obtained in Comparative Example 2, and the CCS-GA-OD hydrogel obtained in Comparative Example 1 was superior to the CCS-OD hydrogel obtained in Comparative Example 3. This indicates that the introduction of GA can synergistically enhance the self-healing efficacy of the hydrogel.

[0050] Swelling rate: Weigh the initial hydrogel (denoted as W0), then immerse it in PBS at room temperature. Periodically remove the hydrogel, dry the surface, and weigh it (denoted as W). t Continue this process until the quality stabilizes, indicating that swelling equilibrium has been reached. Calculate the swelling ratio of the hydrogel using the following formula: Swelling ratio (%) = (W / W) t - W0) / W0 × 100%.

[0051] The results are as follows Figure 6 As shown, the equilibrium swelling ratio of the QCS-GA-OD hydrogel obtained in Example 1 was significantly lower than that of the CCS-GA-OD hydrogel obtained in Comparative Example 1, and the equilibrium swelling ratio of the QCS-OD hydrogel obtained in Comparative Example 2 was significantly lower than that of the CCS-OD hydrogel obtained in Comparative Example 3. The equilibrium swelling ratios of the QCS-OD hydrogel obtained in Comparative Example 2 without gallic acid modification and the CCS-OD hydrogel obtained in Comparative Example 3 were both lower than those of the QCS-GA-OD hydrogel obtained in Example 1 with gallic acid modification and the CCS-GA-OD hydrogel obtained in Comparative Example 1. This result directly reflects the inherent difference in their network structures. 1. Quaternized chitosan QCS system forms a denser cross-linked network: In the QCS-GA-OD hydrogel system obtained in Example 1, in addition to Schiff base bonds, the quaternary ammonium salt groups and oxidized dextran also have strong electrostatic interactions, forming a structure with higher cross-linking density and a denser network, thereby limiting the penetration of water molecules and the expansion of the network. This indicates that compared with CCG, the QCG hydrogel has a more compact network structure and a slower drug release rate, making it easier to achieve a long-acting sustained-release drug delivery process.

[0052] 2. The dual effect of gallic acid (GA) modification on swelling behavior: The swelling ratio of the unmodified hydrogel was significantly lower than that of the modified hydrogel. After gallic acid modification, the large number of polar phenolic hydroxyl groups significantly improved the water absorption and retention capacity of the hydrogel, thus increasing the swelling ratio of the GA-modified hydrogels. However, even after GA modification, the swelling ratio of QCS-GA-OD obtained in Example 1 was still significantly lower than that of CCS-GA-OD obtained in Comparative Example 1. This further confirms that the QCS-based hydrogel network has a high cross-linking density, which allows it to maintain a relatively dense network while possessing a certain degree of hydrophilicity, thus being more conducive to forming a strong binding with the drug and supporting stable sustained-release behavior.

[0053] Depend on Figure 5 , Figure 6 The results readily apparent: the QCS-GA-OD hydrogel obtained in Example 1 significantly outperformed the hydrogels obtained in Comparative Examples 1-3. The gallic acid-modified quaternized chitosan exhibited excellent self-healing properties and low swelling. This low swelling indicates that the QCS-GA-OD hydrogel possesses a dense network structure, which is more conducive to delaying drug diffusion and achieving long-term sustained release, avoiding network relaxation or drug burst release problems caused by excessive swelling. Therefore, using gallic acid-modified quaternized chitosan loaded with glycyrrhizin can achieve a long-term sustained-release drug delivery process, thereby improving drug bioavailability.

[0054] The following experiments were conducted on the blank hydrogel and the hydrogel loaded with glycyrrhizin obtained in Example 1: 1. Physicochemical property characterization 1.1 Scanning Electron Microscope The obtained hydrogel samples were rapidly frozen with liquid nitrogen, and their internal structure was exposed using the liquid nitrogen brittle fracture method, followed by freeze-drying. After being sputter-coated with gold, the microstructure of the freeze-dried samples was observed using a scanning electron microscope (SU8010).

[0055] The results are as follows Figure 7 As shown, the cross-section of the OCG hydrogel exhibits a uniform and interconnected macroporous structure with thin, smooth pore walls, forming an open three-dimensional porous network; its surface is relatively flat with only a few wrinkles. In contrast, the LF-OCG hydrogel has a significantly smaller and more unevenly distributed pore size, with some pores filled by deposits, thickened pore walls exhibiting a rough granular morphology, and a more dense and uniform overall structure with no obvious macropores. These structural differences suggest that the introduction of glycyrrhizin flavonoids occupies some of the pores in the hydrogel and promotes the densification of the network structure. This change may help improve the mechanical stability of the hydrogel and regulate its drug release rate.

[0056] 1.2 Rheology Hydrogels were tested using a parallel plate geometry rotary rheometer in a small-amplitude oscillation mode. The linear viscoelastic region was first determined by amplitude scanning, followed by frequency scanning under constant small strain to record the changes in storage modulus (G') and loss modulus (G'') with frequency.

[0057] result( Figure 8 The results show that G' in both OCG and LF-OCG is consistently higher than G'', with no intersection points, indicating that both are elastically dominant and network-stable three-dimensional gels. After drug loading, G' / G'' shifts upwards overall, especially with an increase in G', resulting in enhanced network stiffness while maintaining the gel state. This suggests the existence of non-covalent interactions such as hydrogen bonding / electrostatic interactions between the drug and the matrix, improving the effective crosslinking density and mechanical stability.

[0058] 1.3 Swelling rate Weigh the initial hydrogel (denoted as W0), then immerse it in PBS at room temperature. Periodically remove the hydrogel, dry the surface, and weigh it (denoted as W). t Continue this process until the quality stabilizes, indicating that swelling equilibrium has been reached. Calculate the swelling ratio of the hydrogel using the following formula: Swelling ratio (%) = (W / W) t - W0) / W0 × 100%.

[0059] The results are as follows Figure 9 As shown, loading glycyrrhizin enhances the swelling capacity of the hydrogel. This phenomenon suggests that the introduction of glycyrrhizin increases the hydrophilicity or porosity of the polymer network, or reduces the effective crosslinking density, thereby promoting the water absorption behavior of the hydrogel. The increased swelling degree means enhanced hydrophilicity and more open network channels within the hydrogel, which facilitates the gradual diffusion and release of the loaded drug in the physiological environment, avoiding the problem of incomplete drug release caused by an overly dense network. This structural change promotes drug diffusion, indicating that glycyrrhizin-loaded hydrogels have the potential for faster drug release.

[0060] 1.4 Self-healing performance test The prepared OCG and LF-OCG hydrogels were placed in culture dishes, and the hydrogels were cut completely in half with a scalpel. The cut surfaces were then joined together and left to stand at room temperature for a period of time to observe the changes in the appearance of the hydrogels.

[0061] The results are as follows Figure 10 As shown, the two halves of the hydrogel, after being cut, can heal back into a complete whole after standing, and there is no obvious interface at the bonding interface, indicating that the hydrogel system has good self-healing properties.

[0062] 1.5 Injectability Evaluation The prepared OCG and LF-OCG ungelled solutions were each placed into a 1 mL syringe and allowed to stand until completely gelled. Then, the solutions were slowly squeezed out through the syringe and the letters "ZCMU" were written on a flat glass plate.

[0063] The results are as follows Figure 11 As shown, both hydrogels can be smoothly extruded from a fine needle and maintain their intact shape, clearly indicating that “ZCMU” can be written, demonstrating their good injectability.

[0064] 2. LF-OCG in vivo distribution and retention experiment SD rats were randomly divided into two groups (n = 4 per group), and were administered either an LF solution containing 1 mg / mL of the fluorescent dye ICG or an LF-OCG solution by gavage. Following administration, fluorescence imaging was performed at different time points (3, 6, 24, and 48 h) using a PerkinElmer in vivo imaging system. The imaging parameters were set as follows: excitation wavelength 745 nm, emission wavelength 820 nm, and exposure time 10 s. Furthermore, animals were sacrificed at 24 h and 48 h post-administration, and the stomach, intestines, and major organs were collected for in vitro fluorescence imaging analysis.

[0065] Studies have shown that in vivo imaging results revealed that in the LF group, fluorescence signals were mainly concentrated in the stomach and small intestine regions within 3–24 hours after gavage, gradually weakening over time and essentially disappearing by 48 hours; while the LF-OCG group exhibited significant sustained-release characteristics, with strong fluorescence signals still detectable even after 24 hours and 48 hours. Figure 12 A). Ex vivo imaging and quantitative analysis showed that the gastric fluorescence intensity of LF-OCG at 24 h and 48 h was significantly higher than that of the LF group ( Figure 12 B, C), suggesting that it can effectively prolong the retention time of glycyrrhizin in the stomach (compared to the LF group, * p <0.05, ** p <0.01, *** p <0.001).

[0066] 3. LF-OCG in vitro release experiment 2 mL of LF-OCG and LF solution were placed into dialysis bags (10000 Da) and then into beakers containing 30 mL of 50% ethanol-based simulated gastric or intestinal fluid, respectively. Under constant temperature and magnetic stirring at 37 ± 1 °C, 2 mL samples were taken at different time points, and an equal volume of fresh release medium was added to maintain a constant total volume. The LF concentration was determined by UV absorption spectroscopy (408 nm), and the cumulative release rate (Er) was calculated using the following formula: Er% = Ci × V1 + (Ci + Ci + … + Ci-1) × V2m × 100% Where Ci is the sample concentration, V1 is the total volume of the release medium, V2 is the sampling volume, and m is the total mass of the drug. The results are as follows Figure 13 As shown, the release rate of LF-OCG before 24 hours was lower than that of the LF group, exhibiting a sustained-release characteristic; however, after 24 hours, both its release rate and cumulative release amount surpassed those of the LF group, demonstrating a long-acting release advantage (compared to the LF group, * p <0.05,** p <0.01, *** p <0.001).

[0067] 4. In vitro biocompatibility testing 4.1 CCK-8 assay for cell viability Gastric mucosal epithelial cells (GES-1) and normal human colonic epithelial cells (NCM-460) were cultured in RPMI-1640 medium containing 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin. Cells were seeded at a density of 8 × 10³ cells / well in 96-well plates and cultured for 24 h. Then, 100 μL of complete medium containing different concentrations of LF or LF-OCG (0, 2.5, 5, 10, 20, 40 μg / mL) was added to each well, and incubation continued for another 24 h. Subsequently, CCK-8 solution was added to each well, and after 3 h of incubation, absorbance was measured at 450 nm to assess cell viability.

[0068] 4.2 Scratch Test After seeding GES-1 cells in 6-well plates and culturing for 24 h, vertical scratches were made on the cell monolayer using a sterile 200 μL pipette tip. After gentle washing with PBS to remove detached cells, the cells were treated with serum-free medium containing LF-OCG hydrogel extract. Cell migration in the scratched areas was recorded using a bright-field microscope, and the migration area was calculated using image analysis software.

[0069] The results showed that within the concentration range of 2.5-20 μg / mL, LF and LF-OCG had no significant effect on cell viability. Figure 14 Furthermore, LF-OCG did not significantly alter the migration ability of GES-1 cells, indicating that it has good biocompatibility.

[0070] 5. In vitro gastric ulcer protection experiment of LF-OCG hydrogel 5.1 Cell viability assay GES-1 cells were seeded at a density of 8 × 10³ cells / well in 96-well plates and cultured for 24 h. Cells were then divided into control, model, LF (20 μg / mL), OCG, and LF-OCG groups. After 24 h of treatment, all groups except the control were replaced with ethanol-containing medium, while the control group was replaced with fresh complete medium. Three h after treatment, the cytotoxicity of ethanol to GES-1 cells was assessed using the CCK-8 assay and the Calcein AM / PI double staining kit.

[0071] Studies have shown that both LF and LF-OCG can significantly alleviate ethanol-induced GES-1 cell damage, with LF-OCG showing particularly outstanding protective effects. Figure 15 A, B).

[0072] 5.2 Intracellular ROS Detection After appropriate treatment, GES-1 cells were digested and collected, washed twice with PBS, and then incubated in serum-free medium containing 1 μM DCFH-DA at 37°C in the dark for 30 minutes. After incubation, the cells were washed three times with PBS, resuspended, and then analyzed.

[0073] The results showed that LF, OCG, and LF-OCG could significantly reduce ethanol-induced increases in intracellular ROS levels and abnormal mitochondrial membrane potential, with LF-OCG showing the most significant effect. Figure 16 Compared to the Control group, # p <0.05, ## p <0.01, ### p <0.001; compared to the Model group, * p <0.05, ** p <0.01, *** p <0.001).

[0074] 6. In vivo anti-gastric ulcer effect of LF-OCG in a rat model SPF-grade male SD rats were randomly divided into six groups (n = 6): a normal control group (Control), a model group (Model), a glycyrrhizin flavonoid group (LF, 20 mg / kg), a hydrogel group (OCG, 5 mL / kg), an LF-OCG group (2 mL / kg, equivalent to LF 20 mg / kg), and an omeprazole group (OME, 20 mg / kg). Except for the normal and model groups, which received an equal volume of physiological saline (5 mL / kg), all other groups were administered the drug via gavage once daily for 7 days. Two hours after the last administration, except for the normal group, all other groups were administered anhydrous ethanol (5 mL / kg) via gavage to induce an acute gastric ulcer model. The mouse modeling procedure is as follows: Figure 17 Two hours after modeling, rats were sacrificed, and gastric tissue was removed. Gastric juice was collected for pH testing. The stomach was then dissected along the greater curvature, and the gastric contents were washed with pre-cooled physiological saline. The gastric tissue was then unfolded and photographed to record the condition of the gastric mucosa. A portion of the gastric tissue sample was removed and fixed in 4% paraformaldehyde, while the remaining tissue was stored at -80℃ for later use. Subsequently, the heart, liver, spleen, lungs, and kidneys of the rats were removed, weighed, and organ indices were calculated. These organs were then fixed in 4% paraformaldehyde. The fixed tissues were embedded in paraffin, sectioned routinely, stained with hematoxylin and eosin (H&E), and observed for histopathological changes under an optical microscope.

[0075] The results are as follows Figure 18 As shown, after anhydrous ethanol was administered via gavage to induce a gastric ulcer model, the gastric mucosa of rats in the Model group showed damage characterized by mucosal congestion, edema, punctate and linear hemorrhages, and erosion. Both LF-OCG and OME interventions improved anhydrous ethanol-induced gastric ulcers and significantly reduced the ulcer area in rats (compared to the Model group, * p <0.05, ** p <0.01, *** p <0.001).

[0076] H&E staining results are as follows Figure 20 As shown, compared with the Control group, the Model group exhibited gastric mucosal epithelial cell shedding, mucosal hemorrhagic injury, submucosal edema, focal necrosis, and inflammatory cell infiltration. Compared with the Model group, the LF-OCG group significantly reduced the pathological changes induced by ethanol. Figure 19 Furthermore, LF-OCG administration did not affect the pH of gastric juice (compared to the Model group, * p <0.05, ** p <0.01, *** p <0.001).

[0077] H&E staining and pathological analysis of major organs in rats showed that no pathological changes or inflammatory cell infiltration were observed in any of the treatment groups, and no significant changes were found in organ indices among the groups. Figure 21 ).

[0078] 7. Detection of oxidative and inflammatory factors in rat gastric tissue Approximately 100 mg of rat stomach tissue was taken, rinsed thoroughly in pre-cooled PBS, and then minced. A homogenate was prepared by adding PBS at a 1:9 ratio. The homogenate was centrifuged at 12000 rpm for 10 minutes at 4°C, and the supernatant was collected. The levels of IL-1β, IL-6, and TNF-α were detected using an ELISA kit; the activities of GSH, MDA, and SOD were determined according to the respective kit instructions. Results are as follows: Figure 22 As shown (compared to the Control group), # p <0.05, ## p <0.01, ### p <0.001; compared to the Model group, * p <0.05, ** p <0.01, *** p <0.001).

[0079] Inflammation is an important pathological feature of gastrointestinal injury, with TNF-α, IL-1β, and IL-6 acting as major pro-inflammatory factors that can delay ulcer repair. This study found that, compared with the model group, LF-OCG significantly reduced the levels of TNF-α, IL-1β, and IL-6 in gastric tissue. Figure 22 AC). Furthermore, GSH, SOD, and MDA are key indicators of the endogenous antioxidant defense system, playing important roles in scavenging free radicals and maintaining intracellular redox balance. Compared to the model group, LF-OCG treatment significantly increased the activity of GSH and SOD while decreasing MDA content, indicating significant antioxidant and anti-inflammatory effects. Figure 22 DE).

Claims

1. A method for preparing a hydrogel loaded with glycyrrhizin flavonoids, characterized in that, The preparation method includes the following steps: Step S1: Quaternized chitosan, gallic acid and crosslinking agent are reacted and freeze-dried to obtain gallic acid-modified quaternized chitosan; Step S2: Dextran reacts with an oxidizing agent and is freeze-dried to obtain oxidized dextran; Step S3: Dissolve the gallic acid-modified quaternized chitosan and the oxidized dextran in a buffer solution to obtain a gallic acid-modified quaternized chitosan solution and an oxidized dextran solution; dissolve glycyrrhizin in an organic solvent to obtain a glycyrrhizin solution. Step S4: Mix the gallic acid-modified quaternized chitosan solution, the oxidized dextran solution, and the glycyrrhizin solution together. After the reaction is complete, a hydrogel loaded with glycyrrhizin is obtained.

2. The method for preparing the hydrogel loaded with glycyrrhizin according to claim 1, characterized in that, The crosslinking agent in step S1 includes 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and / or N-hydroxysuccinimide.

3. The method for preparing the hydrogel loaded with glycyrrhizin according to claim 2, characterized in that, The molar ratio of the quaternized chitosan, the gallic acid, the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and the N-hydroxysuccinimide is 1:1:1:

1.

4. The method for preparing the hydrogel loaded with glycyrrhizin according to claim 1, characterized in that, The buffer solution in step S2 includes a phosphate buffer solution, and the organic solvent includes dimethyl sulfoxide.

5. The method for preparing the hydrogel loaded with glycyrrhizin according to claim 1, characterized in that, In step S3, the concentration of the gallic acid-modified quaternized chitosan solution is 10-30 mg / ml, the concentration of the oxidized dextran solution is 30-70 mg / ml, and the concentration of the glycyrrhizin flavonoid solution is 200-400 mg / ml.

6. The method for preparing the hydrogel loaded with glycyrrhizin according to claim 5, characterized in that, The concentration of the gallic acid-modified quaternized chitosan solution is 20 mg / ml, and the concentration of the oxidized dextran solution is 50 mg / ml.

7. The method for preparing the hydrogel loaded with glycyrrhizin according to claim 1, characterized in that, The gallic acid-modified quaternized chitosan solution and the oxidized dextran solution in step S4 are mixed at a volume ratio of 1:

1.

8. A hydrogel loaded with glycyrrhizin prepared by any one of the preparation methods of claims 1-7.

9. The use of the hydrogel loaded with glycyrrhizin according to claim 8 in the preparation of a medicament for treating acute gastric ulcers.

10. A pharmaceutical preparation, characterized in that, It includes the hydrogel loaded with glycyrrhizin as described in claim 8, and pharmaceutically acceptable excipients.